An Overview of IoT Solutions in Climate Smart Agriculture for Food Security in Sub Saharan Africa: Challenges and Prospects - Dibal, Peter; Onwuka, Elizabeth; Suleiman, Zubair; Salihu, Bala; Nwankwo, Emmanuel; Okoh, Supreme (EAI Endorsed Transactions on Internet of Things, 2022)
INTRODUCTION: Climate smart agriculture (CSA) which involves the integration of IoT and cloud computing is an emerging agricultural paradigm that is foreseen to be the main driver of agriculture as the 21st century progresses. Sub-Saharan Africa lags in this regard and therefore deserves a special focus. OBJECTIVES: This paper presents an overview of Internet-of-Things (IoT) solutions in CSA in the context of food security in sub-Saharan Africa (SSA) METHODS: An overview of the status of food insecurity in SSA and associated factors is presented. The paper then focused on IoT as a technology and how it can be used for CSA in SSA through use cases; possible challenges were also examined. RESULTS: The paper showed that with CSA, SSA can become a net exporter of food. CONCLUSION: The paper concludes with open issues like the funding of research and development which must be addressed if SSA is to leverage IoT technology to attain food security.